2004
DOI: 10.1111/j.0014-3820.2004.tb01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs of Insecticide Resistance in Natural Breeding Sites of the Mosquito Culex Pipiens

Abstract: Genetic changes conferring adaptation to a new environment may induce a fitness cost in the previous environment. Although this prediction has been verified in laboratory conditions, few studies have tried to document this cost directly in natural populations. Here, we evaluated the pleiotropic effects of insecticide resistance on putative fitness components of the mosquito Culex pipiens. Experiments using different larval densities were performed during the summer in two natural breeding sites. Two loci that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 93 publications
(81 reference statements)
1
110
0
Order By: Relevance
“…Another important aspect of insecticide resistance through gene duplication is that at least some of these duplications are actually deleterious in an environment without the pesticide (Raymond et al, 1998;Guillemaid et al, 1999;Bourguet et al, 2004;Foster et al, 2003Foster et al, , 2005. Thus, the impact of gene duplications on fitness can be dependent on the environmental conditions.…”
Section: Beneficial Duplicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect of insecticide resistance through gene duplication is that at least some of these duplications are actually deleterious in an environment without the pesticide (Raymond et al, 1998;Guillemaid et al, 1999;Bourguet et al, 2004;Foster et al, 2003Foster et al, , 2005. Thus, the impact of gene duplications on fitness can be dependent on the environmental conditions.…”
Section: Beneficial Duplicationsmentioning
confidence: 99%
“…Duplications of genes can be beneficial under stressful conditions but deleterious in a benign environment (Brown et al, 1998;Raymond et al, 1998;Guillemaid et al, 1999;Kondrashov et al, 2002;Foster et al, 2003Foster et al, , 2005Bourguet et al, 2004;Francino, 2005;Lawrence, 2005); thus under stressful conditions the fitness function is closer to linear, or at least fast-growing diminishing returns, whereas in a normal setting the function is more of convex or optimum.…”
Section: Dosage Theory and Gene Duplicationsmentioning
confidence: 99%
“…The cost of insecticide resistance has been described both in selected laboratory strains and in field resistant populations (Bourguet et al 2004;Gassmann et al 2009). Resistance costs can be estimated in two major ways (Roux et al 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance costs can be estimated in two major ways (Roux et al 2005a). The first one consists of directly comparing the life-history traits associated with fitness, such as survival, reproduction or behavior, of susceptible and resistant individuals (Bourguet et al 2004;Paris et al 2008;Gassmann et al 2009). In mosquitoes, resistances to chemical insecticides were shown to increase development time or to reduce survival, fecundity, wing length or mating success (De Oliveira et al 2003;Bourguet et al 2004;Berticat et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that emergence percentage of the susceptible strain was significantly greater than that of the Kdr-resistant strains in an insecticide-free environment (Berticat et al 2008). AChE1-resistant strains were associated with a longer development time and shorter wing length (Bourguet et al 2004).…”
Section: Discussionmentioning
confidence: 95%